Pendidikan Akhlak dalam Perspektif Al-Qur’an - Mahmudi; Noerlitasari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research examines the concept of moral education in the Al-Quran and its relevance in the context of modern education. Using the literature study method, this research analyzes verses of the Al-Quran and related commentaries to explore the fundamental principles of moral education. The research results show that the Al-Quran presents a comprehensive concept of morals, including spiritual, moral and social dimensions. The main principles of moral education identified include example (uswatun hasanah), habituation (ta'widiyah), advice (mau'izhah), and attention (mulahazha). Verses related to moral education are classified into three categories: morals towards Allah, fellow humans, and the environment. Implementing the concept of Al-Quran moral education in a modern context requires an adaptive and contextual approach, including the family environment, educational institutions and society. This research concludes that the integration of Qur'anic moral values ​​into the education system can be an effective solution in facing moral challenges in the era of globalization and digitalization.